Extrusion of grass silage and its effect on feed intake, milk production and ingestive behaviour of dairy cows - Managos, Markos (2020)
Grass and clover ley is the main forage crop in Sweden, however, its restrictive role in feed intake limits the total amount included in the diet of a dairy cow. This study examined the effect of extrusion on grass silage intake, milk production, ingestive behaviour and rumen pH. Eight Swedish Red dairy cows in mid/late lactation were fed grass silage of early or late harvest, extruded or control, in a 4x4 Latin square design with four periods of three weeks. Diets were supplemented with a mix of soybean meal, compound feed and minerals. Extrusion increased daily silage dry matter (DM) intake by 1.84 kg/d (p < 0.001), neutral detergent fibre (NDF) intake by 1.04 kg/d (p < 0.001) and decreased physical effective NDF (peNDF8) intake by 1.37 kg/d (p < 0.001). Total DM intake increased by 1.74 kg/d (p < 0.001) while the dietary DM percentage of peNDF8 decreased by 6.9 units (p < 0.001). Milk yield increased by 1.32 kg/d (p = 0.008), Energy corrected milk (ECM) yield increased by 1.87 kg/d (p = 0.004), milk protein concentration increased by 0.09 percentage units (p < 0.001) while total fat and protein production increased by 72.4 g/d (p = 0.015) and 73.7 g/d (p < 0.001), respectively. Extrusion decreased average rumen pH by 0.1 units (p = 0.008). The time rumen pH was below 5.8 increased by 2.97 h/d (p = 0.038) while the curve area below this cut-off point was not affected (p = 0.166). Rate of intake of silage DM and NDF was increased by 20.3 and 11.3 g/min respectively (p < 0.001), daily silage eating time decreased by 0.6 h/d (p = 0.006) and daily rumination time decreased by 1.96 h/d (p < 0.001). Daily chewing time decreased by 2.49 h/d (p < 0.001), with rumination and chewing time per kg of silage NDF intake, decreased by 18.9 and 26.3 min/kg (p < 0.001) respectively. In conclusion, extrusion increased silage intake, eating rate and milk production but decreased chewing activity.